(untitled) (Journal of the College of Basic Education, 2024)
The research aims to identify the degree of performance motivation prepare educational units, and the effect of the Idea Gardens strategy among first-stage students at the University College of Knowledge/Department of Physical Education and Sports Sciences. The researchers assumed that there are no statistically significant differences between the pre- and post-tests in performance motivation and learning the two tapping skills. The researchers used the experimental method to design the control and experimental groups with pre- and post-tests. The research sample included the students of the first stage, numbering (198) students. The research sample included the two experimental B sections (65) and the control C students , numbering (60 ). (a student . The researchers used the Idea Gardens strategy and applied its steps within organized educational units. The number of educational units reached one unit per week. The implementation of the curriculum began on Monday, corresponding to 12/25/2023, and ended on Monday, corresponding to February 26, 2024. After the end of the experiment, the researchers concluded that the Idea Gardens strategy It made the students a primary focus of the lesson, which led to positive interaction among them and participation during the lesson period. Researchers recommend diversity in the use of modern strategies by the teacher in order to encourage students to learn skills, obtain excitement, suspense, and desire to learn, and stay away from boredom.